Fatores neurotróficos na epilepsia de lobo temporal - Erika Machado Viana (2019)
Background: Epilepsy is one of the most common neurological diseases affecting 0.5 to 2% of the population worldwide. Temporal lobe epilepsy (TLE) is the most common epileptic syndrome in adults and is often refractory to antiepileptic drugs. Its etiopathogenesis is complex and not fully understood. The neurotrophic factors brain derived neurotrophic factor (BDNF) and glia derived neurotrophic factor (GDNF) may play a role in the pathophysiology of epilepsy. This study aimed to investigate sociodemographic and clinical characteristics of patients with (TLE) and their association with plasma levels of BDNF and GDNF. Methods: Sixty-six patients with TLE and 52 healthy controls were enrolled in the study. Patients underwent a systematic clinical and psychiatric assessment, and plasma levels of BDNF and GDNF were measured in the interictal period. The patients were subdivided into subgroups according to clinical characteristics such as seizure types and frequency, duration of epilepsy, current antiepileptic treatment, results of neuroimaging studies and presence of cormorbid depressive symptoms. Results: There was no difference between plasmatic BDNF and GDNF in patients with TLE compared to controls. Reduced plasmatic levels of BDNF were observed in patients with longer history of TLE, but not in association to other parameters. Plasma levels of BDNF and GDNF were not different in patients or controls with depression. Conclusion: Low plasma levels of BDNF seem to be associated with long-term ELT.